Mobile use, stress, sleep disturbances, and symptoms of depression in the medical profession: a cross-sectional study - Vasanthakumaran, Tamilarasy (International Journal Of Community Medicine And Public Health, 2018)
Background: With the use of mobile phones increasing in the current generation, it is vital to analyze its negative effects on both mental and physical health. Methods: A questionnaire was given to 120 participants both studying and working in the medical profession. Assessment of the correlation between the use of their mobile device and health was made with mobile phone variables and mental health outcomes (including sleep disturbance, stress and depression). The Pittsburgh Sleep Quality Index (PSQI), Perceived Stress Scale (PSS) and the Centre for Epidemiologic Studies Depression Scale (CES-D) were the scales use to assess these correlations. Results: Results showed a correlation between the hours of use on mobile devices and health aspects. Among the study population, 89.1% owned a single mobile device and 10.9% owned more than one mobile phone. Daily use among these individuals varied from 30 minutes to over 5 hours of use per day. Features used on mobile phones were most commonly communication (94.1%), Internet (92.4%) and social media (90.8%). Conclusions: Statistically significant correlation is seen between mobile phone usage and stress, sleep disturbance and symptoms of depression.